Municipally Owned Enterprises as Danger Zones for Corruption? How Politicians Having Feet in Two Camps May Undermine Conditions for Accountability. (4th May 2019) - Bergh, Andreas; Erlingsson, Gissur; Gustafsson, Anders; Wittberg, Emanuel
Abstract : The market-inspired reforms of New Public Management have been particularly pronounced in Swedish local government. Notably, municipally owned enterprises (MOEs) have rapidly grown in numbers. Principal-agent theory gives rise to the hypothesis that the massive introduction of MOEs has impacted negatively on the conditions for accountability in Swedish local government. To study this, social network analysis was employed in mapping networks for 223 MOEs in 11 strategically chosen municipalities, covering a total of 732 politicians. The analysis reveals substantial overlaps between principals (representatives of the ultimate stakeholders, citizens) and agents (the boards of the MOEs). Hence, corporatization of public services seems to imply worrisome entanglements between the politicians who are set to steer, govern, and oversee MOEs on the one hand, and the board members of MOEs on the other. The increasing numbers of MOEs may therefore have adverse effects on accountability in important and growing parts of Swedish local government.